(Not) Lost in Translation: Psychological Adaptation Occurs During Speech Translation. Issue 1 (January 2021) - Meier, Tabea; Boyd, Ryan L.; Mehl, Matthias R.; Milek, Anne; Pennebaker, James W.; Martin, Mike; Wolf, Markus; Horn, Andrea B.
While language style is considered to be automatic and relatively stable, its plasticity has not yet been studied in translations that require the translator to "step into the shoes of another person." In the present study, we propose a psychological model of language adaptation in translations. Focusing on an established interindividual difference marker of language style, that is, gender, we examined whether translators assimilate to the original gendered style or implicitly project their own gendered language style. In a preregistered study, we investigated gender differences in language use in TED Talks ( N = 1, 647) and their translations ( N = 544) in same- versus opposite-gender speaker/translator dyads. The results showed that translators assimilated to gendered language styles even when in mismatch to their own gender. This challenges predominating views on language style as fixed and fosters a more dynamic view of language style as also being shaped by social context.